Strategi Penanaman Karakter Disiplin Melalui Penegakan Tata Tertib dan Pembelajaran PPKn di SMKN 5 Surabaya - Abyantara Ahnaf Sujana; Rahmanu Wijaya (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to describe: (1) a strategy for inculcating disciplined character through enforcement of discipline at SMKN 5 Surabaya, and (2) a strategy for inculcating disciplined character through Civics learning at SMKN 5 Surabaya. In this study, the researcher adopted a qualitative technique. This research is based on Thomas Lickona's philosophy of character education. This study focuses on instilling disciplined character in SMKN 5 Surabaya through the enforcement of discipline and learning Civics. Data collection techniques using observation, interviews and documentation. The first stage is observation, interviews are conducted to obtain information related to strategies for inculcating disciplined character through enforcement of rules and learning PPKn and documentation related to the process of enforcing rules and learning PPKn. The results of this study indicate that there are several strategies used in building the character of discipline in students. In terms of enforcing the rules, namely socializing the rules, the school provides a statement stating that parents and students agree to the rules contained in the school, cooperate with all school members in enforcing the rules, provide educational sanctions, seek the root of the problem if there are students who violate the rules. often break the rules and find a way out. Then in the case of Civics learning, the teacher makes a learning contract, provides knowledge about the importance of discipline, tells students about the history of struggle, provides examples, conducts assessments and evaluations. Keywords: strategy, character of discipline, school regulation, PPKn